Two-sample Mendelian randomization analysis investigates causal associations between gut microbiota and attention deficit hyperactivity disorder - Wang, Lei; Xie, Zhihao; Li, Guoliang; Li, Guangyao; Liang, Jianmin (Frontiers in Microbiology, 2023)
Previous research have suggested a link between gut microbiota and attention deficit hyperactivity disorder (ADHD), but their causal relationship has not been elucidated. Aiming to comprehensively investigate their causal relationship and to identify specific causal microbe taxa for ADHD, we conducted a two-sample Mendelian randomization (MR) analysis. Instrumental variables of 211 gut microbiota taxa were obtained from gene wide association study (GWAS), and Mendelian randomization study was carried out to estimate their effects on ADHD risk from PCG GWAS (20183 ADHD cases and 35191 controls) and FinnGen GWAS (830 ADHD cases and 215763 controls). Wald ratio (WR), inverse variance weighted (IVW), MR-Egger, and weighted median were the main methods to analyze causality, and MR results are verified by several sensitive analyses. At locus-wide significance level（p < 1×10-5）, IVW results confirmed that genus Eubacteriumhalliigroup (P = 0.013) and genus RuminococcaceaeUCG013 (P = 0.049) were correlated with the risk of ADHD and genus Butyricicoccus (P = 0.009), genus Roseburia (P = 0.009), genus Desulfovibrio (P = 0.015), genus LachnospiraceaeNC2004group (P = 0.026), genus Romboutsia (P = 0.028) and family Oxalobacteraceae (P = 0.048) were protective factors of ADHD. Weighted median results indicated that genus Butyricicoccus (P = 0.018) was negatively correlated with the risk of ADHD. At genome-wide statistical significance level（p < 5×10-8）, Wald ratio results demonstrated that genus Ruminococcustorquesgroup (P = 0.002) was a risk factor of ADHD, while genus Romboutsia (P = 0.01) and family Peptostreptococcaceae (P = 0.01) had a negative correlation with the risk of ADHD. Analysis of heterogeneity (P > 0.05) and pleiotropy (P > 0.05) confirmed the robustness of MR results. We demonstrated that there was a potential causal relationship between some gut microbiota and ADHD. Our research provides a foundation for understanding the causal relationship between gut microbiota and ADHD, and the several gut bacteria found in this study that may reduce the occurrence of ADHD may have potential in the prevention and treatment of ADHD.